Gambaran Tingkat Pengetahuan dan Perilaku Sadari pada Wanita Usia Subur di Wilayah Puskesmas Pajang - Winda Safitri; Ida Nur Imamah; Dyah Rahmawatie Ratna Budi Utami (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Breast cancer is the leading cancer affecting women, with 2.3 million diagnoses and 670,000 deaths globally in 2022. In Indonesia, there were 66,271 cases, representing 30.1% of all cancer cases. Early detection, such as through Breast Self-Examination (BSE) to identify breast lumps, can reduce mortality. BSE is effective for Women of Childbearing Age (15-49 years). However, early breast cancer detection rates remain suboptimal, potentially influenced by the knowledge and behavior of women of childbearing age regarding BSE. Objective: To determine the overview of the level of knowledge and behavior of Breast Self-Examination (BSE) among Women of Childbearing Age in the Pajang Public Health Center area. Methods: This study employed a quantitative descriptive method using purposive sampling. The population consisted of 7,538 Women of Childbearing Age, and the sample comprised 99 respondents. Results: The majority of Women of Childbearing Age in the Pajang Public Health Center area demonstrated a good level of knowledge about BSE, with 52 respondents (52.5%). Furthermore, most respondents exhibited good BSE behavior, with 65 respondents (65.7%). Conclusion:  The majority of respondents had good SADARI knowledge and good  Breast Self-Examination (BSE)  behavior.